The official Ubuntu server book - Rankin, Kyle (Prentice Hall, 2014)
Ubuntu Server is the Linux server for human beings: a complete, free server operating system that just works, with the extra Ubuntu polish, innovation, and simplicity that administrators love. Now, there's a definitive, authoritative guide to getting up-and-running quickly with the newest, most powerful versions of Ubuntu Server